2014
DOI: 10.1107/s2052252514020181
|View full text |Cite
|
Sign up to set email alerts
|

Location of Cu2+in CHA zeolite investigated by X-ray diffraction using the Rietveld/maximum entropy method

Abstract: Accurate structural models of reaction centres in zeolite catalysts are a prerequisite for mechanistic studies and further improvements to the catalytic performance. The Rietveld/maximum entropy method is applied to synchrotron powder X-ray diffraction data on fully dehydrated CHA-type zeolites with and without loading of catalytically active Cu2+for the selective catalytic reduction of NOxwith NH3. The method identifies the known Cu2+sites in the six-membered ring and a not previously observed site in the eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 38 publications
12
144
0
1
Order By: Relevance
“…From such quantifications, it is evident that [Cu(OH)] + -Z species primarily convert to Cu 2+ -2Z and perhaps a portion to CuO x clusters at aging temperatures ≤700 • C. The former transformation, as described by Reaction (3), is also found for the current state-of-the-art commercial Cu/SSZ-13 catalyst ( Figure 5) [18]. At aging temperatures of 750 • C and above, Cu 2+ -2Z stabilizes at~1.2 wt % indicating that this portion of Cu 2+ must be located in windows of 6MRs with paired Al sites; that is, at the energetically most stable locations for Cu 2+ -2Z [33]. The remaining Cu 2+ species are less stable, ultimately converting to CuO x at higher aging temperatures.…”
Section: Hydrothermal Agingsupporting
confidence: 55%
See 1 more Smart Citation
“…From such quantifications, it is evident that [Cu(OH)] + -Z species primarily convert to Cu 2+ -2Z and perhaps a portion to CuO x clusters at aging temperatures ≤700 • C. The former transformation, as described by Reaction (3), is also found for the current state-of-the-art commercial Cu/SSZ-13 catalyst ( Figure 5) [18]. At aging temperatures of 750 • C and above, Cu 2+ -2Z stabilizes at~1.2 wt % indicating that this portion of Cu 2+ must be located in windows of 6MRs with paired Al sites; that is, at the energetically most stable locations for Cu 2+ -2Z [33]. The remaining Cu 2+ species are less stable, ultimately converting to CuO x at higher aging temperatures.…”
Section: Hydrothermal Agingsupporting
confidence: 55%
“…Unless Cu is present at levels exceeding the ion-exchange capacities of the particular SSZ-13 composition used, the current general consensus is that, in the freshly prepared specimens, Cu is present as isolated ions, including Cu 2+ balanced by two nearby framework negative charges (abbreviated as Cu 2+ -2Z, where Z represents a charged zeolite framework site) and a [Cu(OH)] + species balanced by one framework negative charge (as [Cu(OH)] + -Z) [17,[31][32][33]. It is also generally agreed, based on almost identical X-ray absorption near edge structure (XANES) spectra with model Cu salt solutions, that these ions are fully solvated as [Cu(H 2 O) 6 ] 2+ and [Cu(OH)(H 2 O) 5 ] + complexes in hydrated ambient samples [20,34,35].…”
Section: Transformations Of Cu Active Speciesmentioning
confidence: 99%
“…These two locations for the Cu ions are well known from structural analysis of Cu-CHA catalysts, although some controversy exists on which form actually constitutes the active site. 6,12,28,34,[39][40][41]44,52,72,73 However, when adsorbates are present, the Cu ion is lifted out of the 6-ring plane and the preference for the 6-ring location diminishes. 42,43,74 This is also observed for the formation of Cu 2+ −NO 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 (step 1), where the difference in energy for the Cu located in the 8-ring is only 0.08 eV lower compared to the Cu in the 6-ring, showing that there is no real preference for location of the Cu in the 6-ring or 8-ring in this case.…”
Section: Verification Of the Reaction Schemementioning
confidence: 99%
“…Recently, it has been shown that the Cu ions in a Cu-CHA zeolite are located in both the 6-and 8-rings of the chabazite framework structure. 28,29,34,41 Upon adsorption of NH 3 , NO or H 2 O on the Cu atoms in the 6-rings, the Cu atoms are lifted out from their original position into the larger cavities in the zeolite, [42][43][44] and therefore it seems that the SCR reaction actually takes place in the large cavities in Cu-CHA. However, only the Cu ions located in or close to the 6-rings seem to contribute to the SCR activity in Cu-CHA.…”
Section: Mechanistic Aspects Of the Scr Reactionmentioning
confidence: 99%
“…For Cu-SSZ-13, there are several XAS and XRD studies combined with computational modelling that suggest Cu in positions close to six or eight membered rings in the zeolite pores [14,15]. Under reaction conditions though, reactive gases are expected to adsorb at the Cu sites and therefore change coordination number, geometry and oxidation state of these sites.…”
Section: Resultsmentioning
confidence: 99%